2019
DOI: 10.1177/0269216319847089
|View full text |Cite
|
Sign up to set email alerts
|

What socio-economic factors determine place of death for people with life-limiting illness? A systematic review and appraisal of methodological rigour

Abstract: Background: Socio-economic factors play important roles in place of death. However, up-to-date knowledge on socio-economic determinants for place of death is warranted including analysis of collinearity between socio-economic determinants. Aim: To examine associations between socio-economic determinants (social class, deprivation level in area of residence, income, education, occupation, urbanisation) and place of death among adult patients with life-limiting illnesses. Furthermore, to describe how these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
(338 reference statements)
3
22
1
Order By: Relevance
“…Regarding the excesses of deaths in hospital vs. home, significantly higher values were observed in the most deprived CT, especially in respiratory disease, Alzheimer's disease, malignant neoplasm, heart disease, and other non-palliative causes. In all cases, an association was observed between living in areas with greater deprivation and probability of dying in hospital, as indicated by previous studies [11,19,31,32]. This is an important result since death at home is usually considered an indicator of the quality of palliative care services [3,10].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regarding the excesses of deaths in hospital vs. home, significantly higher values were observed in the most deprived CT, especially in respiratory disease, Alzheimer's disease, malignant neoplasm, heart disease, and other non-palliative causes. In all cases, an association was observed between living in areas with greater deprivation and probability of dying in hospital, as indicated by previous studies [11,19,31,32]. This is an important result since death at home is usually considered an indicator of the quality of palliative care services [3,10].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, recent studies have also explored the relationship between place of death and aggregate indicators of socioeconomic deprivation [11,19] with the areas of greatest deprivation being those with the highest hospital mortality rates. Furthermore, various studies seem to indicate that social differences have a lesser effect on the place of death when measured at the individual level (for example, educational level) than when measured at the aggregate level (commonly by means of deprivation at the area level) [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to the end of life could be culturally different in a rural setting compared to an urban one. A recent systematic review oriented to analyse the socio-economic factors determining the place of death found that dying at home was associated with living in rural areas but, potential causes remain unsolved [32]. Mean survival time among patients who died in our study was slightly higher among the urban ones.…”
Section: Mortalitycontrasting
confidence: 45%
“…The decision to die at home allows patients to maintain control over their lives. The approach to the end of life is culturally different in a rural setting compared to an urban one 33 . For instance, rural patients could be more in favor of dying at home and not prolonging their lives through hospitalizations and aggressive interventions.…”
Section: Mortalitymentioning
confidence: 99%